Single atom catalysts and their preparation and application in reverse water gas shift reaction

By using carbon material-supported single-atom catalysts in the reverse water gas transformation reaction, the problems of poor stability of traditional catalysts and low carbon monoxide selectivity at high temperatures are solved, and efficient carbon monoxide conversion and thermal stability of the catalyst are achieved, reducing costs.

CN116173998BActive Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111419985.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-26
Publication Date
2025-02-14
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

The existing counterwater gas conversion reaction catalysts have poor stability at high temperatures, which are prone to sintering or excessive carbon monoxide hydrogenation to form methane, reducing the selectivity of carbon monoxide, and precious metal catalysts have problems of poisoning and high cost.

Method used

The carbon material-supported single-atom catalyst is prepared by mixing metal precursors, oxygen-containing chelating agents, solvents and carbon support, solid-liquid separation, drying and calcination, etc., to avoid the use of precious metals and carbon monoxide poisoning.

Benefits of technology

It achieves a high carbon monoxide selectivity under the counterwater gas transformation reaction conditions, avoids the formation of methane, and has good thermal stability and low cost, making it suitable for large-scale preparation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalyst development, and relates to the preparation of a single-atom catalyst and its application in the reverse water-gas shift reaction. The present invention adopts a roasting method to prepare a carbon material-loaded non-precious metal single-atom catalyst, and the metal loading is 1 to 10 wt% (in terms of metal), which has good reverse water-gas shift activity. The present invention utilizes the characteristics of single-atom isolated sites to avoid the occurrence of carbon dioxide methanation side reactions; at the same time, the heteroatoms on the surface of the carrier can anchor the metal single atoms, so that it has good thermal stability. The present invention develops a method for preparing a carbon material-loaded single-atom catalyst, which does not use precious metals, has a wide source of raw materials, is low in cost, and is suitable for large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst development, in particular to the preparation of a single-atom catalyst and its application in a reverse water-gas shift reaction, belonging to relevant technologies for the comprehensive utilization of carbon dioxide. Background Art

[0002] With the rapid development of the chemical industry in recent years, the emission of carbon dioxide (CO2) has been increasing, the concentration of carbon dioxide in the atmosphere has been rising, and the greenhouse effect caused by it has become increasingly serious. How to effectively convert carbon dioxide into usable resources has become an urgent problem for researchers to solve. Therefore, the field of carbon dioxide conversion and utilization has become the focus of many researchers. Among them, the reverse water gas shift reaction (RWGS) reaction is one of the most valuable carbon dioxide conversion reactions. It refers to the reaction in which carbon dioxide and hydrogen form carbon monoxide and water under the action of a catalyst. The produced carbon monoxide can be converted into clean liquid fuels and high-value-added chemicals through the Fischer-Tropsch synthesis (FTS) pathway, and then carbon dioxide can be hydrogenated to produce clean liquid fuels and high-value-added chemicals (CO2-FTS), thereby realizing the clean and efficient utilization of carbon resources.

[0003] Generally speaking, the reverse water-gas shift reaction is a reversible reaction. The catalysts suitable for the water-gas shift reaction (WGS) are usually also suitable for the reverse water-gas shift reaction. Traditional catalysts for the reverse water-gas shift reaction mainly include copper-based catalysts, nickel-based catalysts and precious metal catalysts, and there are fewer reports on other types of catalysts. The reverse water-gas shift reaction is a typical endothermic reaction (ΔH 298K = +41.2 kJ·mol -1 ), high temperature is conducive to the conversion of carbon dioxide and the formation of carbon monoxide. Although copper-based catalysts have good reverse water-gas shift reaction activity, they are prone to sintering at high temperatures, which affects the activity and stability of the catalyst, so they are not suitable for reverse water-gas shift reaction at high temperatures. Although the stability of nickel-based catalysts is better than that of copper-based catalysts, the carbon monoxide generated by the reverse water-gas shift reaction is prone to over-hydrogenation to produce methane, thereby reducing the selectivity of carbon monoxide. Precious metal catalysts have good activity and stability, but precious metals are prone to carbon monoxide poisoning. On the other hand, the high price of precious metals also limits their large-scale application. Summary of the Invention

[0004] The present invention aims to provide a method for preparing a carbon-supported single-atom catalyst. The single-atom catalyst prepared using the present invention exhibits good carbon monoxide selectivity under the reverse water-gas shift reaction conditions (200-600°C, 0.1-1.0 MPa). The use of a single-atom catalyst prevents the generated carbon monoxide from hydrogenating on the catalyst surface to form species such as methane. Furthermore, the absence of precious metals also avoids carbon monoxide poisoning of precious metal catalysts.

[0005] To achieve the above objectives, the present invention adopts the following scheme.

[0006] The present invention provides a method for preparing a single-atom catalyst, which comprises the following steps.

[0007] A method for preparing a single-atom catalyst, characterized in that the method comprises the following steps:

[0008] (1) mixing a metal precursor, an oxygen-containing chelating agent, a solvent, and a carbon support, allowing the mixture to stand for solid-liquid separation, and drying the solid insoluble matter to prepare a supported metal-chelating agent complex;

[0009] (2) mixing the nitrogen-containing ligand and the solvent with the supported metal-chelate complex prepared above, allowing the mixture to stand for solid-liquid separation, and drying the solid insoluble matter to prepare a supported single-atom catalyst precursor;

[0010] (3) calcining the single-atom catalyst precursor prepared above to obtain a supported single-atom catalyst.

[0011] Based on the above technical solution, in step (1), in step (1), the metal precursor is one or more of the chloride, nitrate, sulfate, formate, acetate, and citrate of metal Co, Cu, and Mn, preferably one or more of chloride, nitrate, and acetate; the oxygen-containing chelating agent is one or more of D-glucose, D-mannose, D-fructose, D-xylose, and D-galactose, preferably one or more of D-glucose, D-fructose, and D-xylose; The solvent is one or more of tetrahydrofuran, petroleum ether, water, methanol, and ethanol, preferably one or more of water, methanol, and ethanol; the carbon carrier is one or more of activated carbon, carbon nanotubes, carbon nanofibers, ordered mesoporous carbon, graphite, carbon black, and carbon spheres, preferably one or more of carbon nanotubes, carbon nanofibers, and ordered mesoporous carbon; the drying temperature is 40 to 150° C., preferably 60 to 120° C.; and the drying time is 0.5 to 6.0 h, preferably 1.0 to 3.0 h.

[0012] Based on the above technical solution, in step (2), the nitrogen-containing ligand is one or more of melamine, o-phenanthroline, triethylamine, o-aminoazotoluene, pyrrolidine, glycine, and glutamic acid, preferably one or more of melamine, triethylamine, and glycine; the solvent is one or more of tetrahydrofuran, petroleum ether, water, methanol, and ethanol, preferably one or more of water, methanol, and ethanol; the drying temperature is 40 to 150° C., preferably 60 to 120° C.; and the drying time is 0.5 to 6.0 h, preferably 1.0 to 3.0 h.

[0013] Based on the above technical solution, the ratio of each substance in steps (1) and (2) is metal precursor: oxygen-containing chelating agent: carbon support: nitrogen-containing ligand = 1:1:10:1 to 10:10:10:10 (mass ratio), preferably 1:1:10:1 to 5:8:10:8 (mass ratio).

[0014] Based on the above technical solution, grinding or ultrasonic mixing is adopted.

[0015] Based on the above technical solution, in step (3), the calcination atmosphere is one or more of nitrogen, argon, helium, carbon monoxide, and carbon dioxide, preferably one or more of nitrogen, argon, and carbon dioxide; the calcination gas flow rate is 10 to 500 mL min -1 , preferably 20 to 250 mL min -1 The heating rate from room temperature to drying temperature to calcination temperature is 1-10℃·min -1 , preferably 1~5℃·min -1 ; The calcination temperature is 600-1200°C, preferably 700-1000°C; the calcination time is 0.2-8.0h, preferably 1.0-4.0h.

[0016] Another aspect of the present invention provides the use of the above-mentioned supported single-atom catalyst in the reverse water-gas shift reaction.

[0017] Based on the above technical solution, in the application, the reaction temperature is 200-600°C (preferably 300-550°C), the reaction pressure is 0.1-1.0 MPa (preferably 0.1-0.5 MPa), and the gas space velocity (based on the mass of the catalyst) is 1000-8000 mL·gcat. -1 ·h -1 (Preferably 2000 to 6000 mL gcat -1 ·h -1 ), the molar ratio of H2 to CO2 in the raw gas is 1.0 to 4.0 (preferably 1.0 to 2.0); the reactor adopts a fixed bed, the feeding method adopts continuous feeding, the product first passes through a cold tank to remove the generated water, and the tail gas is analyzed by gas chromatography.

[0018] The present invention uses a calcination method to prepare a carbon-supported non-precious metal single-atom catalyst, with a metal loading of 1 to 10 wt% (calculated as metal), exhibiting excellent reverse water-gas shift activity. This method utilizes the properties of isolated single-atom sites to avoid the occurrence of carbon dioxide methanation side reactions. Furthermore, heteroatoms on the support surface can anchor metal atoms, imparting excellent thermal stability. This method develops a method for preparing a carbon-supported single-atom catalyst that avoids the use of precious metals, utilizes a wide range of raw material sources, is low-cost, and is suitable for large-scale production.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) A method for preparing carbon-supported non-precious metal single-atom catalysts has been developed, which can produce a high-load non-precious metal single-atom catalyst. This method is simple and easy to operate, has a wide range of raw materials, and is suitable for large-scale industrial applications.

[0021] (2) By utilizing the characteristics of isolated sites of single-atom catalysts, excessive hydrogenation of carbon monoxide generated by the hydrogenation of carbon dioxide can be avoided, and higher carbon monoxide selectivity can be obtained compared with the widely used nickel-based catalysts. At the same time, the single atoms on the surface of the catalyst are anchored by the N atoms and O atoms on the surface of the carrier, which can ensure that they do not agglomerate and sinter at high temperatures. Compared with traditional copper-based catalysts, they have good thermal stability. At the same time, no precious metals are used, which saves costs on the one hand and avoids the problem of poisoning and deactivation of precious metals caused by carbon monoxide on the other hand.

[0022] Therefore, the present invention has broad application prospects in the large-scale preparation of non-noble metal single-atom catalysts and in the reverse water-gas shift reaction system. DETAILED DESCRIPTION

[0023] The present invention will be further described below with reference to the examples, but the scope of the present invention is not limited in any way.

[0024] Example 1

[0025] 0.600 g of copper chloride, 0.600 g of D-glucose, 4.200 g of carbon nanotubes and 10.0 g of methanol were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand for 5 min and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 1.5 h to obtain a supported metal-chelate complex; then 0.600 g of melamine, 10.0 g of methanol and the supported metal-chelate complex prepared above were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 2.5 h to obtain a supported single atom catalyst precursor; the prepared supported single atom catalyst precursor was calcined at 900 ° C in an argon atmosphere for 2.5 h (heating rate of 5.0 ° C·min-1 , gas flow rate 180mL·min -1 ) to prepare catalyst A. High-resolution spherical aberration electron microscopy (HAADF-STEM) confirmed that the metal was distributed on the carrier in a monodisperse manner, and inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the metal loading was 6.8 wt%.

[0026] The prepared single-atom catalyst was used to conduct a reverse water-gas shift reaction evaluation test. The specific evaluation conditions are as follows: reaction temperature 450°C, reaction pressure 0.2 MPa, gas space velocity (calculated by catalyst mass) 6000 mL·gcat -1 ·h -1 The molar ratio of H₂ to CO₂ in the feed gas was 1.5. A fixed-bed reactor was used, with continuous feeding. The product was first passed through a cooling tank to remove generated water, and the tail gas was analyzed by gas chromatography. The carbon dioxide conversion and product selectivity are listed in Table 1.

[0027] Example 2

[0028] 0.500 g of cobalt acetate, 0.700 g of D-fructose, 5.000 g of carbon nanofibers and 10.0 g of ethanol were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand for 10 min and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 1.0 h to obtain a supported metal-chelate complex; then 0.700 g of triethylamine, 10.0 g of ethanol and the supported metal-chelate complex prepared above were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 2.0 h to obtain a supported single-atom catalyst precursor; the prepared supported single-atom catalyst precursor was calcined in a nitrogen atmosphere at 800 ° C for 3.0 h (heating rate of 5.0 ° C·min -1 , gas flow rate 150mL·min -1 ) to prepare catalyst B. High-resolution spherical aberration electron microscopy (HAADF-STEM) confirmed that the metal was distributed on the carrier in a monodisperse manner, and inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the metal loading was 5.5 wt%.

[0029] The prepared single-atom catalyst was used to conduct a reverse water-gas shift reaction evaluation test. The specific evaluation conditions are as follows: reaction temperature 500°C, reaction pressure 0.15 MPa, gas space velocity (calculated by catalyst mass) 6000 mL·gcat -1 ·h -1 The molar ratio of H₂ to CO₂ in the feed gas was 1.0. A fixed-bed reactor was used, with continuous feeding. The product was first passed through a cooling tank to remove generated water, and the tail gas was analyzed by gas chromatography. The carbon dioxide conversion and product selectivity are listed in Table 1.

[0030] Example 3

[0031] 1.000 g of manganese acetate tetrahydrate, 1.200 g of D-xylose, 5.000 g of ordered mesoporous carbon and 10.0 g of water were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand for 15 min and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 1.5 h to obtain a supported metal-chelate complex; then 2.000 g of glycine, 10.0 g of ethanol and the supported metal-chelate complex prepared above were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 2.5 h to obtain a supported single atom catalyst precursor; the prepared supported single atom catalyst precursor was calcined in a carbon dioxide atmosphere at 850 ° C for 1.5 h (heating rate of 4.0 ° C·min -1 , gas flow rate 160mL·min -1 ) to prepare catalyst C. High-resolution spherical aberration electron microscopy (HAADF-STEM) confirmed that the metal was distributed on the carrier in a monodisperse manner, and inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the metal loading was 6.5 wt%.

[0032] The prepared single-atom catalyst was used to conduct a reverse water-gas shift reaction evaluation test. The specific evaluation conditions are as follows: reaction temperature 400°C, reaction pressure 0.15 MPa, gas space velocity (calculated by catalyst mass) 6000 mL·gcat -1 ·h -1 The molar ratio of H₂ to CO₂ in the feed gas was 1.5. A fixed-bed reactor was used, with continuous feeding. The product was first passed through a cooling tank to remove generated water, and the tail gas was analyzed by gas chromatography. The carbon dioxide conversion and product selectivity are listed in Table 1.

[0033] Example 4

[0034] 1.100 g of cobalt nitrate hexahydrate, 1.100 g of D-glucose, 4.300 g of ordered mesoporous carbon and 10.0 g of water were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand for 30 min and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 1.5 h to obtain a supported metal-chelate complex; then 1.600 g of melamine, 10.0 g of methanol and the supported metal-chelate complex prepared above were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 2.5 h to obtain a supported single atom catalyst precursor; the prepared supported single atom catalyst precursor was calcined in a nitrogen atmosphere at 850 ° C for 3.5 h (heating rate of 5.0 ° C·min -1 , gas flow rate 150mL·min-1 ) to prepare catalyst D. High-resolution spherical aberration electron microscopy (HAADF-STEM) confirmed that the metal was distributed on the carrier in a monodisperse manner, and inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the metal loading was 7.5 wt%.

[0035] The prepared single-atom catalyst was used to conduct a reverse water-gas shift reaction evaluation test. The specific evaluation conditions are as follows: reaction temperature 550°C, reaction pressure 0.10 MPa, gas space velocity (calculated by catalyst mass) 6000 mL·gcat -1 ·h -1 The molar ratio of H₂ to CO₂ in the feed gas was 1.0. A fixed-bed reactor was used, with continuous feeding. The product was first passed through a cooling tank to remove generated water, and the tail gas was analyzed by gas chromatography. The carbon dioxide conversion and product selectivity are listed in Table 1.

[0036] Example 5

[0037] 1.200 g of copper nitrate trihydrate, 1.500 g of D-fructose, 6.100 g of carbon nanofibers and 10.0 g of ethanol were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand for 20 min and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 1.0 h to obtain a supported metal-chelate complex; then 1.600 g of triethylamine, 10.0 g of methanol and the supported metal-chelate complex prepared above were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 2.5 h to obtain a supported single atom catalyst precursor; the prepared supported single atom catalyst precursor was calcined at 900 ° C in an argon atmosphere for 2.0 h (heating rate of 5.0 ° C·min -1 , gas flow rate 180mL·min -1 ) to prepare catalyst E. High-resolution spherical aberration electron microscopy (HAADF-STEM) confirmed that the metal was distributed on the carrier in a monodisperse manner, and inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the metal loading was 6.9 wt%.

[0038] The prepared single-atom catalyst was used to conduct a reverse water-gas shift reaction evaluation test. The specific evaluation conditions are as follows: reaction temperature 500°C, reaction pressure 0.15 MPa, gas space velocity (calculated by catalyst mass) 6000 mL·gcat -1 ·h -1 The molar ratio of H₂ to CO₂ in the feed gas was 2.0. A fixed-bed reactor was used, with continuous feeding. The product was first passed through a cooling tank to remove generated water, and the tail gas was analyzed by gas chromatography. The carbon dioxide conversion and product selectivity are listed in Table 1.

[0039] Example 6

[0040] 0.900 g of manganese chloride, 1.200 g of D-xylose, 7.100 g of carbon nanofibers and 10.0 g of methanol were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand for 50 min and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 1.0 h to obtain a supported metal-chelate complex; then 2.600 g of melamine, 10.0 g of methanol and the supported metal-chelate complex prepared above were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 2.0 h to obtain a supported single atom catalyst precursor; the prepared supported single atom catalyst precursor was calcined at 800 ° C in an argon atmosphere for 2.0 h (heating rate of 5.0 ° C·min -1 , gas flow rate 120mL·min -1 ) to prepare supported catalyst F. High-resolution spherical aberration electron microscopy (HAADF-STEM) confirmed that the metal was distributed on the support in a monodisperse manner, and inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the metal loading was 6.6 wt%.

[0041] The prepared single-atom catalyst was used to conduct a reverse water-gas shift reaction evaluation test. The specific evaluation conditions are as follows: reaction temperature 500°C, reaction pressure 0.20 MPa, gas space velocity (calculated by catalyst mass) 6000 mL·gcat -1 ·h -1 The molar ratio of H₂ to CO₂ in the feed gas was 2.0. A fixed-bed reactor was used, with continuous feeding. The product was first passed through a cooling tank to remove generated water, and the tail gas was analyzed by gas chromatography. The carbon dioxide conversion and product selectivity are listed in Table 1.

[0042] Example 7

[0043] 1.500 g of cobalt chloride, 2.300 g of D-glucose, 6.500 g of activated carbon and 10.0 g of ethanol were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand for 60 min and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 1.5 h to obtain a supported metal-chelate complex; then 2.500 g of triethylamine, 10.0 g of ethanol and the supported metal-chelate complex prepared above were placed in a 50 mL beaker, stirred and mixed thoroughly, ultrasonicated, allowed to stand and then centrifuged, and the insoluble matter was dried in an oven at 80 ° C for 2.5 h to obtain a supported single atom catalyst precursor; the prepared supported single atom catalyst precursor was calcined in a nitrogen atmosphere at 800 ° C for 3.0 h (heating rate of 5.0 ° C·min -1 , gas flow rate 140mL·min -1) to prepare catalyst G. High-resolution spherical aberration electron microscopy (HAADF-STEM) confirmed that the metal was distributed on the carrier in a monodisperse manner, and inductively coupled plasma optical emission spectroscopy (ICP-OES) showed that the metal loading was 7.0 wt%.

[0044] The prepared single-atom catalyst was used to conduct a reverse water-gas shift reaction evaluation test. The specific evaluation conditions are as follows: reaction temperature 500°C, reaction pressure 0.10 MPa, gas space velocity (calculated by catalyst mass) 6000 mL·gcat -1 ·h -1 The molar ratio of H₂ to CO₂ in the feed gas was 3.0. A fixed-bed reactor was used, with continuous feeding. The product was first passed through a cooling tank to remove generated water, and the tail gas was analyzed by gas chromatography. The carbon dioxide conversion and product selectivity are listed in Table 1.

[0045] Comparative Example 1

[0046] Patent CN107570162B discloses a nickel-based catalyst for the reverse water-gas shift reaction and its preparation method. More specifically, the loading amount of metal Ni in the catalyst is 1 to 10wt%, and four groups of samples with metal loading amounts of 1wt%, 2wt%, 5wt% and 10wt% were tested for reaction activity. The results show that when the metal loading amount is less than 5wt%, the reverse water-gas shift reaction activity is low, but the carbon monoxide selectivity is high; when the metal loading amount is 5wt%, the reverse water-gas shift reaction activity is the highest, but the methane selectivity is greater than 10%. Taking a metal loading amount of 5wt% as a comparative example, the specific evaluation conditions are a reaction temperature of 600°C, a reaction pressure of 0.10MPa, and a gas space velocity (based on catalyst mass) of 5000mL·gcat -1 ·h -1 The molar ratio of H2 to CO2 in the raw gas is 1.0. The carbon dioxide conversion rate and the selectivity of each product are listed in Table 1.

[0047] Table 1 Reverse water-gas shift reaction performance of different single-atom catalysts

[0048] Catalyst No. <![CDATA[CO2 conversion rate (%)]]> CO selectivity (%) <![CDATA[CH4 selectivity (%)]]> A 34.1 82.2 17.8 B 25.3 92.6 7.4 C 30.5 88.8 11.2 D 61.3 95.8 4.2 E 28.8 85.6 14.4 F 24.5 87.1 12.9 G 40.7 98.5 1.5 Comparative Example 32.1 89.5 10.5

[0049] Unless otherwise specified, the raw materials and equipment used in the present invention are commonly used in the art; the methods used in the present invention are conventional methods in the art unless otherwise specified.

[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a single atom catalyst, characterized in that: The method comprises the following steps: (1) mixing a metal precursor, an oxygen-containing chelating agent, a solvent and a carbon carrier, allowing the mixture to stand for solid-liquid separation, and drying the solid insoluble matter to prepare a supported metal-chelating agent complex; (2) mixing the nitrogen-containing ligand, the solvent and the supported metal-chelating agent complex prepared above, allowing the mixture to stand for solid-liquid separation, and drying the solid insoluble matter to prepare a supported single-atom catalyst precursor; (3) calcining the single atom catalyst precursor prepared above to obtain a supported single atom catalyst; In step (1), the metal precursor is one or more of the chloride, nitrate, sulfate, formate, acetate and citrate of metal Co, Cu and Mn; the oxygen-containing chelating agent is one or more of D-glucose, D-mannose, D-fructose, D-xylose and D-galactose; the solvent is one or more of tetrahydrofuran, petroleum ether, water, methanol and ethanol; the carbon carrier is one or more of activated carbon, carbon nanotubes, carbon nanofibers, ordered mesoporous carbon, graphite, carbon black and carbon spheres; the drying temperature is 40-150 °C; the drying time is 0.5-6.0 h; In step (2), the nitrogen-containing ligand is one or more of melamine, o-phenanthroline, triethylamine, o-aminoazotoluene, pyrrolidine, glycine, and glutamic acid; the solvent is one or more of tetrahydrofuran, petroleum ether, water, methanol, and ethanol; the drying temperature is 40-150 °C; and the drying time is 0.5-6.0 h.

2. The preparation method according to claim 1, characterized in that: In steps (1) and (2), the drying temperature is 60-120°C; and the drying time is 1.0-3.0 h.

3. The preparation method according to claim 1, characterized in that: The ratio of the substances in steps (1) and (2) is: the mass ratio of metal precursor: oxygen-containing chelating agent: carbon carrier: nitrogen-containing ligand = 1:1:10:1~10:10:10:

10.

4. The preparation method according to claim 3, characterized in that: The mass ratio of metal precursor: oxygen-containing chelating agent: carbon support: nitrogen-containing ligand = 1:1:10:1~5:8:10:

8.

5. The preparation method according to claim 1, characterized in that: In steps (1) and (2), the mixture is fully mixed by grinding or ultrasonication; and the standing time is more than 2 minutes.

6. The preparation method according to claim 1, characterized in that: In step (3), the calcination atmosphere is one or more of nitrogen, argon, helium, carbon monoxide, and carbon dioxide; the calcination gas flow rate is 10~500 mL×min -1 ; The heating rate from room temperature to drying temperature to roasting temperature is 1~10 °C×min -1 ; Calcination temperature is 600~1200 °C; Calcination time is 0.2~8.0 h.

7. The preparation method according to claim 6, characterized in that: Roasting gas flow rate 20~250 mL×min -1 ; The heating rate from room temperature to drying temperature to roasting temperature is 1~5 °C×min -1 ; Calcination temperature is 700~1000 °C; Calcination time is 1.0~4.0 h.

8. Use of the single-atom catalyst synthesized by the preparation method according to claim 1 in the reverse water-gas shift reaction.

9. The use according to claim 8, characterized in that: In the application, the reaction temperature is 200~600 °C, the reaction pressure is 0.1~1.0 MPa, the gas space velocity is 1000~8000 mL×gcat-1×h-1, and the molar ratio of H2 to CO2 in the raw gas is 1.0~4.

0.

10. The use according to claim 9, characterized in that: The reaction temperature is 300~550 °C, the reaction pressure is 0.1~0.5MPa, the gas space velocity is 2000~6000 mL×gcat-1×h-1, and the molar ratio of H2 to CO2 in the raw gas is 1.0~2.

0.

11. The use according to claim 8 or 9, characterized in that: The reactor adopts a fixed bed, and the feeding method adopts continuous feeding. The product first passes through a cold tank to remove the generated water, and the tail gas is analyzed by gas chromatography.

Citation Information

Patent Citations

  • A nickel-based catalyst for reverse water-gas shift reaction and its preparation method

    CN107570162B

  • Ir-based catalyst for reverse water-gas shift reaction as well as preparation and application thereof

    CN106881082A

  • Monoatomically dispersed rhodium-based catalyst, preparation method thereof and application thereof in methane low-temperature oxidation reaction

    CN111195514A